An Observational Study of Immunity Level of Treatment-Naive, HIV-Positive Patients Attending Tertiary Care Centre: A Cross-Sectional Study from North-Western India - Choudhary, Sidhya; Patidar, Nisha; Yadav, Rajeev; Sharma, Babita; Vyas, Nitya (Annals of Pathology and Laboratory Medicine, 2024)
Background: Acquired Immunodeficiency Syndrome (AIDS) poses a significant public health challenge in India, driven by the Human Immunodeficiency Virus (HIV). HIV exhibits a selective affinity for CD4+ T lymphocytes, leading to their gradual destruction, resulting in severe immune depression and an elevated risk of opportunistic infections and cancers. The CD4+ T lymphocyte count serves as a valuable tool for initiating and monitoring the response to antiretroviral therapy. This study investigates the immunological status of newly diagnosed, treatment-naive HIV-positive individuals across diverse demographics and transmission categories, providing valuable insights for tailored intervention strategies in this population. Materials and Methods: This was a cross-sectional study involving 200 newly diagnosed, treatment-naive HIV-positive participants. A structured proforma was used to collect demographic data, education status, occupation, transmission routes, and CD4+ T lymphocyte counts of study participants. Results: Participants had a mean age of 41.02 years, with the majority being under 50 years old (73%). Most were male (66%), and 48% had primary-level education. Heterosexual contact was the primary transmission route (98.5%), including 18% through commercial partners. The mean CD4+ T lymphocyte count was 289.21 cells/mmÂ³, indicating significant immunodeficiency. A majority (73%) were late presenters (CD4+ T lymphocyte counts <350 cells/mmÂ³). Conclusion: The study highlights the high prevalence of late HIV diagnoses, particularly among less educated and socioeconomically deprived populations. The dominance of provider-initiated testing suggests ongoing stigma surrounding voluntary testing. Urgent interventions are needed, focusing on education, occupation-related vulnerabilities, and awareness campaigns to reduce late diagnoses and enhance public health responses to HIV/AIDS.